The usefulness of med expert in differentiating benign and malignant breast lesions - Mazeda, Murad (2008)
Breast cancer incidence is rising and so as the caseloads of the radiologists to intezpzet the mammograms and breast ultrasounds. In an effort to help the radiologis1s, Med Expert was developed Objective: To determine the usefulness ofMed Expert in differentiating breast lesions on mammogram and breast ultrasound by trainee radiologist by comparing the radiologist report and the was compared to the histology I cytology report. The sensitivity, specificity, positive predictive and negative predictive values of radiologist and the trainee radiologist were calculated. Result The sensitivizy, specificity and accuracy of radiologist for mammogram intetpretation were 90%, 700At and 77.5% respectively. For ultrasound it was 96.7%, 72.90/o and 82.1%. The sensitivity, specificity and accuracy of trainee radiologist for intetpretation of mammogram with the aid of Med Expert were 800/o, 96% and 90% respectively. For ultrasowd it was 900/o, 83% and 85.90At respectively There was lower sensitivity but higher specificity obtained by the trainee radiologist using Med Expert compared to the radiologist interpretation However, the overall accuracy of trainee radiologist using Med Expert was higher compared to radiologist The kappa agreement between the radiologist and trainee radiologist for mammogmm was 0.6 and that for the ultrasound was 0.8. Con elusion Med Expert. was useful in diffexentiaring benign and malignant breast lesions. The txainee radiologist was able to provide a higher accuracy of interpretation for both mammogmm and ultrasound, with the aid of the system, compared to the radiologist trainee tadiologist interpretation with the aid ofMed Expert with histopathology or cytology results. Methodology: EtbicaJ approval obtained. This cross sectional study was conducted in Hospital University Sains Malaysia in the period of 18 months starting :from June 2006 till November 2007. A total of 85 patients who had breast lumps and had mammogram and or ultrasound and biopsies done were recruited in the study. The initial mammogram and breast ultrasound report was compared with the histology I cytology report. These images were subsequently re-reported by the trainee radiologist using Med Expert and the output :from the system